Functional Assessment and Identification of the Needs of Children and Students with Attention Deficit Hyperactivity Disorder - Cvetomira Angelova (Педагогически форум)
Functional assessment of child development is an important component in the understanding and support of children and students with attention deficit hyperactivity disorder. This comprehensive assessment provides valuable information on the skills, abilities and challenges faced by a child/student in different areas of their development. By identifying strengths, difficulties and potential areas for support, pedagogical professionals can develop targeted plans and strategies to promote the optimal development and well-being of the child. The article examines the process of functional assessment of child development, the key areas it covers, and the importance of this tool in supporting the development of children with attention deficit hyperactivity disorder.